A Study on Retailers’ Behavior Intention to Accept and Use the Omni channel Commerce Platforms - Nguyen, Thi Thuy; Ha, Van Duong (Journal of Ecohumanism, 2024)
Research on retailers’ behavioral intention to accept and use the omnichannel commerce platforms (OCPs) in the Vietnam context used the Unified Theory of Acceptance and Use of Technology (UTAUT2) model and supplemented the other factors such as omnichannel capability, omnichannel integration. The results of this study show Effort Expectation, Social Influence, Hedonic Motive, Professional Capacity, Seamlessly Linking have a positive impact on retailers’ behavior intention to accept and use OCPs. Behavioral Intention and Favorable Conditions have a positive impact on use behavior. Meanwhile, Habits and Omnichannel Integration have a negative impact on the use behavior of OCPs in Vietnam. The findings of this model help managers and OCPs providers identify factors that influence OCPs’ behavioral intention and use behavior of retailers in Vietnam.